SIFAT-SIFAT RING FAKTOR YANG DILENGKAPI DERIVASI - Iwan Ernanto (Diponegoro University, 2018)
Let R is a ring with unit element and δ is a derivation on R. An ideal I of R is called δ-ideal if it satisfies δ (I)I. Related to the theory of ideal, we can define prime δ-ideal and maximal δ-ideal. The ring R is called δ-simple if R is non-zero and the only δ-ideal of R are 0 and R. In this paper, given the necessary and sufficient conditions for quotient ring R/I is a δ-simple where δ_* is a derivation on R/I such that δ_* ° π =π ° δ.